European Law in an Era of Crisis - Müller-Graff, Peter-Christian; Selvig, Erling (Deutsch-norwegisches Forum des Rechts, 2012)
Foreword; CONTENTS; I. Free Movement of Capital in an Era of Crisis; Reactions to the Crisis and the Rules on the Free Movementof Capital in the EC/EU; Reactions and Rules on the Free Movement of Capitalin EEA-EFTA States in the Crisis Test; II. Free Movement of Services in an Era of Crisis; Homogeneity and Supremacy of the European Law of Free Movementof Financial Services - Reactions and Rules on the Free Movementof Services in the EEA-EFTA States in the Crisis Test; III. Rules on Competition in an Era of Crisis; State Aid and Public Enterprises in Times of Crises
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2010 -- Goslar; Norwegen; Europäische Union; Kapitalverkehrsfreiheit; Finanzkrise